The jurisprudential differences about the Term credit “Al-I’timan” and credit card: Islamic and conventional perspectives - Mohammed Jassem Mohammed,; Rahmah Ismail,; Ruzian Markom, (Institut Kajian Rantau Asia Barat, 2011)
The credit in general and credit card in particular have become important instrument for individuals, merchants and banks. The use of a credit card represents a part of daily activities nowadays; therefore, it has become a duty on the Muslim jurists to clarify the Islamic legal principle (Al-Takyif) for the card. Terminologies have a big impact on the jurisprudential adaptation to the extent that a new contract can be formed depending on the jurisprudential analysis. Therefore, the Muslim jurists differ in the term of credit in Islamic credit card transaction relating to the legitimate proof of the term and suitable description of credit to the card used. The jurists debated on the definition of credit card in the modern banking transaction; many of the view the term credit connotes “Al-I’timan” while others prefer “Al-Qard”. The objective of this article is to discuss comprehensively the adaptation of Islamic terminology to the credit card in the banking transaction. Islamic jurisprudential analytical approach was adopted in justifying the suitable terms of credit to credit card. It also applied the comparative approach in ascertaining the definition of credit card transaction in Islam. Finally, the discussion revealed that the term “Al-I’timan” refers to the term credit in the credit card transaction in Islam.